Design of Switched-Capacitor Filter Circuits using Low Gain Amplifiers - Serra, Hugo Alexandre de Andrade; Paulino, Nuno (SpringerBriefs in Electrical and Computer Engineering,, 2015)
This book describes the design of switched-capacitor filter circuits using low gain amplifiers and demonstrates some techniques that can minimize the effects of parasitic capacitances during the design phase. Focus is given in the design of low-pass and band-pass SC filters, and how higher order filters can be achieved using cascaded biquadratic filter sections. The authors also describe a low voltage implementation of a low-pass SC filter.